Averroës’ Takfīr of al-Ghazālı̄: Ta’wīl and Causal Kufr (American Journal of Islam and Society, 2021)
Al-Ghazālı̄ famously claims in the Incoherence of the Philosophers that al-Fārābī and Avicenna are unbelievers because they hold philosophical positions that conflict with Islam. What is less well-known, however, is that Averroës claims in the Decisive Treatise that al-Fārābī and Avicenna are not unbelievers; rather, al-Ghazālı̄ is the true unbeliever for writing the Incoherence of the Philosophers. In this paper, my aim is to present a sustained reconstruction of Averroës’ legal and philosophical argument for why al-Ghazālı̄ is an unbeliever. The crux of Averroës’ argument is that al-Ghazālı̄ has expressed false allegorical interpretations of scripture to unqualified persons, which has caused them to fall into unbelief. By being causally responsible for other people’s unbelief, al-Ghazālı̄ is an unbeliever as well.